Model Pembelajaran Accelerated Learning Cycle Terhadap Self Concept Matematis Siswa - Rahma Hayati Siregar (Institut Agama Islam Negeri Padangsidimpuan, 2019)
This research is motivated by the mathematical self-concept of students in learning mathematics is not yet formed with positive self concept and this is influenced by many factors, one of which is the teacher factor. A teacher must be able to create a learning atmosphere that is meaningful, fun, creative and dynamic through the use of appropriate learning models one of which is the learning model Accelerated Learning Cycle is a learning model that creates a learning process environment that is meaningful and promotes the emergence of positive emotions. The formulation of the problem is Is there a significant influence on the application of the accelerated learning cycle learning model to students' mathematical self-concepts? This research is a quantitative study using the Quasi-experimental method, the type of experimental design is the quasi experimental design method with the type of Pretest-Posttest Control Group Design in two different classes which are divided into experimental and control classes. class VII 3 totaling 31 students and VII 11 totaling 34 students. Then the data collection instrument was a questionnaire that was given twice, that is before being treated and after being treated. Analysis of the data used is descriptive and inferential statistical formulas namely normality test and hypothesis testing with paired sample t-test. In accordance with the hypothesis testing using the Paired Sample t-test, the value of t thitung = 37.177 is greater than ttabel = 2.03452 then according to the basis of decision making in the t test, it can be concluded that H0 is rejected and Ha is accepted at the 5% significance level (α = 0.05) this shows that there is a significant effect of the application of the accelerated learning cycle learning model to students' mathematical self-concepts